Survival and Inflammatory Response in Adipose-derived Mesenchymal Stem Cell-enriched Mouse Fat Grafts. Issue 12 (December 2016) - Begic, Anadi; Isfoss, Björn L.; Lønnerød, Linn K.; Vigen, Alexander; Moskaug, Jan Ø.
Abstract : Background: Adipose tissue-derived mesenchymal stem cells (ATMSCs) are currently used in grafting procedures in a number of clinical trials. The reconstructive role of such cells in fat graft enrichment is largely unclear. This study was undertaken to assess survival and inflammatory response in fat grafts enriched with ATMSCs in mice. Methods: ATMSC-enriched adipose tissue was grafted subcutaneously in a clinically relevant manner in mice, and survival and inflammatory response were determined by bioluminescence imaging of transgenic tissue constitutively expressing luciferase or driven by inflammation in wild-type animals. Results: Only a minor fraction of ATMSCs transplanted subcutaneously were found to survive long term, yet fat grafts enriched with ATMSCs showed improved survival for a limited period, compared with no enrichment. NF-κB activity was transiently increased in ATMSC-enriched grafts, and the grafts responded adequately to a proinflammatory stimulus. In one animal, cells originating from the subcutaneous graft were found at a site of inflammation distant from the site of engraftment. Conclusion: ATMSCs display limited subcutaneous survival. Still, ATMSC enrichment may improve the outcome of adipose tissue grafting procedures by facilitating short-term graft survival and adequate inflammatory responses. Migration of cells from grafted adipose tissue requires further investigation. Abstract : Supplemental Digital Content is available in the text.